A two-layer box model for the strait of İstanbul using radial basis function collocation - Güngör, Cenk (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
A one-dimensional, two-layer, depth averaged box model was developed to simulate the surface gradient driven steady flow occurring in the Strait of Istanbul (Bosphorus). An efficient meshless numerical scheme based on the Radial Basis Function (RBF) collocation method has been employed in the model. In the model, the currents are driven by the hydrostatic pressure gradient and the bottom slope. Flow resistance is introduced through the bottom shear stress and interfacial shear stress between the layers. Transfer of momentum in the vertical direction is neglected.The model was tested by specifying layer thickness and discharge values at the Black Sea and the Sea of Marmara ends of the strait. The results, presented in the form of graphs of layer depths and velocities along the length of the strait, were found to be in close agreement with those of previous studies and, where available, measurements. The RBF collocation method was found to be a promising method for two- and possibly three-dimensional models of the strait.
Keywords: Fluid dynamic measurements.